Programmed Cell Death-1 (PD-1) anchoring to the GPI-linked co-receptor CD48 reveals a novel mechanism to modulate PD-1-dependent inhibition of human T cells. (April 2023) - White, Della; Cote-Martin, Alexandra; Bleck, Marina; Garaffa, Nicole; Shaaban, Abdulsalam; Wu, Helen; Liu, Dongmei; Young, David; Scheer, Justin; Lorenz, Ivo C.; Nixon, Andrew; Fine, Jay S.; et al.
Abstract: Activation of PD-1 by anchoring it to Antigen Receptor (AR) components or associated co-receptors represents an attractive approach to treat autoimmune conditions. In this study, we provide evidence that CD48, a common lipid raft and Src kinase-associated coreceptor, induces significant Src kinase-dependent activation of PD-1 upon crosslinking, while CD71, a receptor excluded from these compartments, does not. Functionally, using bead-conjugated antibodies we demonstrate that CD48-dependent activation of PD-1 inhibits proliferation of AR-induced primary human T cells, and similarly, PD-1 activation using PD-1/CD48 bispecific antibodies inhibits IL-2, enhances IL-10 secretion, and reduces NFAT activation in primary human and Jurkat T cells, respectively. As a whole, CD48-dependent activation of PD-1 represents a novel mechanism to fine tune T cell activation, and by functionally anchoring PD-1 with receptors other than AR, this study provides a conceptual framework for rational development of novel therapies that activate inhibitory checkpoint receptors for treatment of immune-mediated diseases. Highlights: Programmed cell death protein 1 (PD-1) is a validated immune checkpoint inhibitory receptor in health and disease. Induction of PD-1 activation represents a therapeutic strategy with potential to ameliorate immune-mediated diseases. PD-1 activation by forced co-localization to kinase-rich lipid rafts via an anchor molecule achieves T cell inhibition. This study outlines a novel therapeutic approach for treatment of immune-mediated disease via inhibitory receptor activation.